Information Technology Strategy for Micro, Small, and Medium Enterprises in the Era of Industry 4.0 - Leni Fitriani; Heru Nugroho (IJAIT (International Journal of Applied Information Technology), 2022)
During the industrial revolution 4.0, business and industry competitiveness expanded. Because of circumstances like these, competition between firms or micro, small, and medium enterprises (MSMEs) is also increasing. To create and maintain a competitive advantage, a business must be able to dominate the market by enhancing its strategy. The ability of companies to expand market segments by introducing distribution channels and innovations by employing technical advancements is one of the company's development tactics. To identify potential and difficulties for further study, this article aims to evaluate information technology solutions for empowering Micro, Small, and Medium Enterprises. The Biblioshiny tool was used to conduct the literature review for this article. Results Scientific publications investigate opportunities and obstacles to determine the function that strategic information technology supports in the case study of Micro, Small, and Medium Enterprises.